Reflections on 'Public administrative theory and the separation of powers' - Rosenbloom, David H. (2013)
Published 30 years ago, my article on "Public Administrative Theory and the Separation of Powers" introduced what is often called the "three perspectives" approach or framework for understanding public administration at a macro-level by viewing it through the lenses of management, politics, and law. Each of these perspectives is anchored in a function of government-execution, legislation, and adjudication respectively-which the U S federal level is housed primarily in the institutional structures of the executive branch, Congress, and the courts. The article became something of an "instant classic" and the textbook that followed, Public Administration: Understanding Management, Politics, and Law in the Public Sector (1986), gained widespread adoption. The present article reflects on what the three perspectives framework did, did not do, and whether it is useful in application to the vast changes in public administrative thought and practice that have occurred since its publication. Specifically addressed are whether the framework retains utility in the wake of reinventing government and the advent of collaborative governance as well as how it might be strengthened to inventory and cumulate public administrative knowledge in the future. - Reproduced.
Keywords: Seperation of powers; Public administration